Jenis dan Strategi Pembinaan Organisasi Dakwah dalam Meningkatkan Efektivitas Gerakan Keagamaan - Nasor Nasor; Devi Tias Pratiwi; Mutiara Ramadhani (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
Islamic da'wah organizations play a strategic role in developing, nurturing, and sustaining religious values within society. The development of da'wah organizations is not only related to strengthening religious understanding but also encompasses managerial dimensions, human resource development, and adaptation to social dynamics. This study aims to identify and analyze the types of development implemented within da'wah organizations, as well as their implications for the effectiveness of da'wah movements in the community. This research employs a qualitative method using a literature study approach, through the examination of scholarly works, institutional documents, and previous research. The findings reveal three main forms of development within da'wah organizations: (1) Religious development, which includes strengthening the understanding of Islamic teachings, internalizing moral values, and enhancing members’ spiritual capacity; (2) Managerial and organizational development, focused on institutional structuring, program management, and da'wah strategy development; and (3) Social community development, which involves empowering the community through education, social services, and activities that foster a religious and civilized society. In conclusion, the development of da'wah organizations requires a comprehensive and sustainable approach to effectively respond to social changes and strengthen the organization’s contribution to character building and the advancement of Islamic civilization.